FORMULASI DAN UJI STABILITAS FISIK SEDIAAN MASKER GEL PEEL-OFF EKSTRAK ETANOL DAUN BAYAM MERAH (Amaranthus Tricolor L.) DENGAN BASIS POLIVINIL ALKOHOL - Rusmin, Rusmin (Akademi Farmasi Yamasi Makassar, 2024)
Abstract. The purpose this study was to determine the effect of variations in PVA concentration on the physical characteristics of the peel off gel mask preparation and to determine the concentration of PVA in the peel off gel mask preparation of red spinach leaf extract which can provide good physical characteristics. Red spinach leaves contain flavonoid compounds, saponins and tannins which have antioksidant effect on the skin. Red spinach leaves extract was prepared in a peel off gel mask preparation by varying the concentration of PVA. PVA plays role in the formulation of peel off gel masks because it has adhesive properties. The concentrations of PVA used was 10% b/b, 13% b/b and 16% b/b. Extraction of red spinach leaves was obtained by remaceration method using 96% ethanol as solvent. The physical characteristic tests, drying time test, stability tests, and viscosity tests. Based on the statistical results of One Way Anova the physical characteristics of the peel off gel mask preparation including pH, spread ability, viscosity and drying time, there was a significant difference of 0,000 (sig<0,05). The concentration of PVA in the peel off gel mask preparation of purple leaf extract which can provide good physical characteristics is the concentration of PVA at 13%.